Study on the Improved Electrical and Thermal Performance of the PV/T Façade System - Ruobing Liang; Yan Gao; Peng Wang; Chao Zhou (International Journal of Photoenergy)
This paper is aimed at improving the performance of a building-integrated photovoltaic thermal (BIPV/T) system driven by a refrigerant pump. The research is aimed at optimizing and upgrading the BIPV/T system to address the shortcomings of the original system by replacing roll-bond PV/T units with improved heat transfer features. The system’s connecting form was redesigned using a liquid separator to solve the uneven distribution of the refrigerant on the PV/T façade. We proposed the variable frequency refrigerant pump that can be adjusted to suit the working condition. An experimental study was performed to analyze the electrical and thermal efficiency of the proposed system. The results show that the electrical efficiency of the BIPV/T system was 8% which is 14.3% higher than the traditional BIPV system, while in the test period, the BIPV/T system average COP was 3.4. The thermal and comprehensive efficiencies were 20% and 42%, respectively. Besides, the proposed system’s average COP was 3.7 times greater than the original BIPV/T system.